2014
DOI: 10.1210/jc.2014-1480
|View full text |Cite
|
Sign up to set email alerts
|

Increased Plasma DPP4 Activity Is Predictive of Prediabetes and Type 2 Diabetes Onset in Chinese Over a Four-Year Period: Result From the China National Diabetes and Metabolic Disorders Study

Abstract: DPP4 activity is an important predictor of the onset of insulin resistance, prediabetes, and type 2 diabetes in apparently healthy Chinese individuals. This finding may have important implications for understanding the etiology of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 16 publications
4
47
0
Order By: Relevance
“…Blood lipids, HbA 1c , IL-6, CRP, nitrotyrosine, and 8-iso-PGF2a were measured as previously described (9,10).…”
Section: Clinical and Laboratory Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood lipids, HbA 1c , IL-6, CRP, nitrotyrosine, and 8-iso-PGF2a were measured as previously described (9,10).…”
Section: Clinical and Laboratory Measurementsmentioning
confidence: 99%
“…DPP4 is a widely expressed multifunctional enzyme that exists as a membrane-anchored cellsurface protein or in a soluble form in the plasma (8). Our previous data suggested that increased plasma DPP4 activities were found in type 2 diabetes and promoted the development of hyperglycemia, inflammation, and oxidative stress (9,10). More interestingly, animal studies have proved that DPP4 inhibitors, such as sitagliptin or linagliptin, ameliorated cognitive impairment through suppressing inflammatory reaction or oxidative stress in different models of mice (11,12).…”
mentioning
confidence: 99%
“…Dipeptidyl peptidase-4 (DPP4) is a widely expressed multifunctional exopeptidase that exists as a membrane-anchored cell surface protein or in a soluble form in the plasma. In addition to its catalytic function in the degradation of NPY, it has also been identified as a novel adipokine playing important roles in the development of hyperglycemia, inflammation, and oxidative stress [5,6], all of which have been suggested to be involved in the pathogenesis of depression. More importantly, in our previous longitudinal study [5], DPP4 activity was found to be higher in type 2 diabetic patients than in those with normal glucose tolerance.…”
Section: Figmentioning
confidence: 99%
“…In addition to its catalytic function in the degradation of NPY, it has also been identified as a novel adipokine playing important roles in the development of hyperglycemia, inflammation, and oxidative stress [5,6], all of which have been suggested to be involved in the pathogenesis of depression. More importantly, in our previous longitudinal study [5], DPP4 activity was found to be higher in type 2 diabetic patients than in those with normal glucose tolerance. According to these findings above, we speculate that DPP4 activity may be positively correlated with depression symptoms in type 2 diabetes.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation